The cognitive methodology of the Porto School: foundation and evolution to the present day - Fernandes, Eduardo Jorge Cabral dos Santos (2015)
As a consequence of the international impact of the work of Álvaro Siza Vieira (Pritzker winner in 1992) and Eduardo Souto Moura (Pritzker winner in 2011), the so-called Porto School has become a global phenomenon. But the expression ‘School of Porto’ implies much more than the work of these two architects: it designates an identity that relates the pedagogy of a teaching institution with the ideas and architectural practice of its professors and/or former students.1 The Porto School was born as an idea of Portuguese Modern Architecture with the work of Fernando Távora, between the publication of “O Problema da Casa Portuguesa” (The Problem of the Portuguese House) in 1945 and the building of the Market in Santa Maria da Feira (1954-1959). This individual action (adapting international modern models to Portuguese physical and cultural context) became a collective trend between 1955 and 1961, the years when the Surveys on Portuguese Vernacular Architecture took place. In the early 70s, we find in Siza’s work a non-visual character that reinterprets this identity and anticipates Kenneth Frampton’s definition of ‘critical regionalism’;2 in the 80s, the work of Souto Moura will emerge with a personal interpretation of this idea of School. Today, this identity subsists, as a result of the transmission mechanisms of a cognitive methodology - a way of thinking connected to a way of doing. Nonetheless, the persistence of this idea of School, nowadays, implies the respect for the heritage of its way of thinking but, paradoxically, it also needs a continuous critical exercise concerning the update of this legacy.